Recognition in Communication/Education. Sketches for A Category under Construction - Martínez, Darío Gabriel (2017)
This article presents notions about recognition. The contributions of Axel Honneth, Nancy Fraser and Paul Ricoeur are taken as a starting point. These conceptual positions are combined to reflect on a category of communication/education. The problem of recognition has always been present in this field. Named in one way or another, this question poses a possible recurrence that is to ask about concrete intervention in political-cultural fields, institutions and organizations. For this, it is considered how it has been worked in this field from the works of Paulo Freire and Jorge Huergo.